Ketidakjujuran Akademik Pada Mahasiswa Calon Guru Program Studi Pendidikan Anak Usia Dini - Herdian Herdian; Sri Lestari (Universitas Islam Tribakti Lirboyo Kediri, 2018)
Being a teacher must have a positive character, one of which is honesty. Honesty can be known based on academic behavior during a student. In fact, there are currently many dishonest behaviors in prospective educators, especially in early childhood education program students. The purpose of this study is to describe academic behavior, especially academic dishonesty in students of early childhood education programs at University X in Central Java, Indonesia. The focus of research is on forms of dishonest behavior when working on Tasks, Middle Semester Exams and final semester examinations, and the causes of dishonesty occur. This study uses a phenomenological qualitative approach with a data collection tool with in-depth interviews. The research subjects were 4 students in the 7th semester who took courses in the Teacher Education Study Program and Early Childhood Education. The results showed that the form of academic dishonesty in prospective students of early childhood teacher educators was asking for answers, asking for the essence of answers, seeing answers (without being known by friends), bringing cheats and searching for answers on the internet. Academic dishonesty factor is caused by the question that comes out when the exam is not studied or not in accordance with what is learned when studying, does not know the answer, does not understand the material delivered during lectures and learning is not optimal.